Novel Hujan Bulan Juni Karya Sapardi Djoko Damono dan Madrasah Cinta Karya Ayu Nesia (Kajian Intertekstual) - Anggraini, Tri Riya; Awalludin, Awalludin; Basuki, Basuki (LPPM STKIP PGRI Bandar Lampung, 2024)
The aim of this research is to identify the similarities and differences between the two in Sapardi Djoko Damono's novel